Knowledge, Attitude, and Perception regarding antibiotic use and its associated resistance among the general public in Lahore, Pakistan. - Momina Ikram; Muhammad Aaliyan Khan; Haris Javed; Muhammad Asif Shareef; Iqra Mushtaq; Muhammad Ashraf Choudhary (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Increasing misuse and irrational prescribing of antibiotics by physicians has led to antimicrobial resistance (AMR) posing a major global threat. Furthermore, only a few studies have been conducted to evaluate this domain in Pakistan. The objective of this study is to assess the general public’s knowledge, attitude, and perception towards antibiotic use and its resistance, and to determine positive associations between the various socio-demographic variables.METHODOLOGY: A descriptive cross-sectional study was conducted from October 2022 to March 2023. A convenient sampling technique was employed, selecting participants ≥ 18 years of age (n= 339). Structured questionnaires were distributed on different study sites and random participants were asked to respond immediately.RESULTS: Results showed that assessing antibiotics use among these 342 participants in the last year, it was determined that the majority of them had only used antibiotics once 108(31.6%). A closer number of individuals had used antibiotics more than thrice 101(29.5%)  shows no significant association between rural and urban with a p-value=0.941>0.05. The majority were also aware of fatal allergic reactions produced by some antibiotics and agreed to stop antibiotic use if any adverse reaction were to occur 277(81.0%)p-value=0.674>0.05. No significance was observed, although some near-significant values of importance were noted and discussed. CONCLUSION: Antibiotic usage is commonly observed among all individuals; however, views contain many deviations. Constraints, including sample bias, Lahore’s urban dominance, and the omission of doctor-prescribing evaluations, highlight the study's limitations and have further skewed our results.